Effects of Joint Action Observation on Children’s Imitation - Nejra Rizvanović; Ildikó Király; Natalie Sebanz (Behavioral Sciences)
Grasping others’ intentions from their actions is essential for learning, as it enhances the ability to identify collaborative acts and anticipate others’ actions, facilitating effective coordination toward shared goals. From a young age, children seem to recognize when others are working together based on their interactions and use this understanding to inform their own learning. Although much of early learning occurs in joint contexts, little attention has been devoted to understanding how children learn by participating in joint actions and by observing others acting together. Using a puzzle box paradigm, we tested 3–6-year-old children’s imitation of an inefficient performance following individual and joint demonstrations in which the inefficient performance did or did not involve bimanual or joint coordination. This allowed us to test whether the tendency to overimitate extends to joint actions and how action coordination modulates imitative behavior. We found that overimitation extends to joint actions, as indicated by similar rates of inefficient copying following individual and joint action demonstrations. Furthermore, our results suggest that action coordination did not play a significant role in modulating children’s tendency to overimitate. Taken together, the results of the study advance our understanding of how learning occurs in social interactions.